Global real‐time dose measurements using the Automated Radiation Measurements for Aerospace Safety (ARMAS) system. Issue 11 (18th November 2016) - Tobiska, W. Kent; Bouwer, D.; Smart, D.; Shea, M.; Bailey, J.; Didkovsky, L.; Judge, K.; Garrett, H.; Atwell, W.; Gersey, B.; Wilkins, R.; Rice, D.; et al.
Abstract: The Automated Radiation Measurements for Aerospace Safety (ARMAS) program has successfully deployed a fleet of six instruments measuring the ambient radiation environment at commercial aircraft altitudes. ARMAS transmits real‐time data to the ground and provides quality, tissue‐relevant ambient dose equivalent rates with 5 min latency for dose rates on 213 flights up to 17.3 km (56, 700 ft). We show five cases from different aircraft; the source particles are dominated by galactic cosmic rays but include particle fluxes for minor radiation periods and geomagnetically disturbed conditions. The measurements from 2013 to 2016 do not cover a period of time to quantify galactic cosmic rays' dependence on solar cycle variation and their effect on aviation radiation. However, we report on small radiation "clouds" in specific magnetic latitude regions and note that active geomagnetic, variable space weather conditions may sufficiently modify the magnetospheric magnetic field that can enhance the radiation environment, particularly at high altitudes and middle to high latitudes. When there is no significant space weather, high‐latitude flights produce a dose rate analogous to a chest X‐ray every 12.5 h, every 25 h for midlatitudes, and every 100 h for equatorial latitudes at typical commercial flight altitudes of 37, 000 ft (~11 km). The dose rate doubles every 2 km altitude increase, suggesting a radiation event management strategy for pilots or air traffic control; i.e., where event‐driven radiation regions can be identified, they can be treated like volcanic ash clouds to achieve radiation safety goals with slightly lower flight altitudes or more equatorial flight paths. Key Points: The ARMAS fleet of six instruments can measure the ambient radiation environment at commercial aircraft altitudes at any point on the planet Small radiation "clouds" in specific magnetic latitude regions have been identified Dose rate doubles every 2 km altitude higher (or halves every 2 km lower), which points to an aviation radiation risk management pathway